2012
DOI: 10.1371/journal.pone.0044356
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and Time Use during Occupational Therapy and Nutrition/Dietetics Clinical Education: A Cohort Study

Abstract: BackgroundCurrently in the Australian higher education sector higher productivity from allied health clinical education placements is a contested issue. This paper will report results of a study that investigated output changes associated with occupational therapy and nutrition/dietetics clinical education placements in Queensland, Australia. Supervisors’ and students’ time use during placements and how this changes for supervisors compared to when students are not present in the workplace is also presented.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
2
11
1
Order By: Relevance
“…Not surprisingly, student OOS increased across Weeks 1-5 of the placement block. This is in contrast with findings in previous studies, 8,13 where no change in OOS during clinical placements was reported for the student-supervisor team in the case of occupational therapy and dietetic students. Although the differences were not statistically significant, Rodger et al 13 demonstrated that the number of OOS had periods of growth during placements of longer length (10-14 weeks), with the main growth occurring between Weeks 1 and 3.…”
Section: Discussioncontrasting
confidence: 99%
“…Not surprisingly, student OOS increased across Weeks 1-5 of the placement block. This is in contrast with findings in previous studies, 8,13 where no change in OOS during clinical placements was reported for the student-supervisor team in the case of occupational therapy and dietetic students. Although the differences were not statistically significant, Rodger et al 13 demonstrated that the number of OOS had periods of growth during placements of longer length (10-14 weeks), with the main growth occurring between Weeks 1 and 3.…”
Section: Discussioncontrasting
confidence: 99%
“…Limitations of this research include the poor response and restriction to Queensland, so caution should be exercised in interpreting the results, which may limit representativeness. Our combined data with occupational therapy students with higher numbers show similar results in ICM . It was unfortunate that supervisors in the second half of the ICM placement did not participate in the data collection despite repeated attempts to encourage them to do so.…”
Section: Discussionsupporting
confidence: 52%
“…Our combined data with occupational therapy students with higher numbers show similar results in ICM. 11 It was unfor-tunate that supervisors in the second half of the ICM placement did not participate in the data collection despite repeated attempts to encourage them to do so. Many of these supervisors were in regional and remote areas and in smaller facilities with possibly more complex roles and fewer staff, and thus less likely to have time to participate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the conventional model, education remains focussed on profession-specific knowledge and skills. Detailed descriptions of conventional clinical education and its strengths and limitations in specific professional groups can be found elsewhere (Dahlenburg, 2006;Lekkas et al, 2007;Mannix, Faga, Beale, & Jackson, 2006;Rodger et al, 2012).…”
Section: Controlmentioning
confidence: 99%